Toxicity of untreated wood leachates towards two saltwater organisms (Crassostrea gigas and Artemia franciscana) - LIBRALATO, Giovanni; VOLPI GHIRARDINI, Annamaria; LOSSO C (Journal of Hazardous Materials, 2007)
Wood is widely used in the development of freshwater, estuarine and marine coastlines. Timbers last according to their content of naturally occurring preservatives (mostly phenols and aldehydes), produced to prevent decay from biotic agents. When untreated woods are exposed to aquatic media, leachates are generated with likely toxic effects on the target environment. The potential impact on saltwaters of leachates from some untreated timbers of both native and tropical species has been assessed. The leaching procedure was set up considering British Standard test methods for paints and OECD guidelines for wood preservatives emission scenarios. Toxicity was monitored via the acute toxicity test with the brine shrimp Artemia franciscana and the sub-chronic embryotoxicity test with the oyster Crassostrea gigas. Brine shrimps evidenced no toxic effects while oysters discriminated well among leachates: the tropical wood species showed similar or relatively lower toxic effects than the native ones according to both leaching cycles (24 and 72 h). The ecotoxicological data have been integrated with some physical and chemical parameters.